Characteristics of personal exposure to polycyclic aromatic hydrocarbons in public transportation microenvironments in Beijing(In Chinese) - M* Zheng; CQ Yan; QY Yang; XH* Qiu; HY Fu; XY Li; T. Zhu (Research of Environmental Sciences, 2014)
Characteristics and sources of particle-bound polycyclic aromatic hydrocarbons (PAHs) in PMin three typical transportation microenvironments were investigated, and the health risks were assessed. Fine particle exposure by pedestrians and commuters taking buses and subways were collected using personal exposure samplers in December 2011 in Beijing. Concentrations of multiple PAHs were measured by gas chromatography-mass spectrometry (GC-MS). Sources of PAHs were identified by distribution patterns and ratios of different PAHs. Health risk assessments associated with respiratory exposure to PAHs were conducted based on benzopyrene (BaP) equivalent concentrations (BEQ), BaP based equivalent carcinogenic power (BaPE) and inhalation cancer risk. The results showed that:1) The average exposure level of PAHs in roadside, buses, and subways were (120±119), (101±46.6), and (50.8±25.6) ng/m, respectively. 2) The similarity of PAHs distribution patterns in the three transportation microenvironments and the ratios of PAHs ρ(Flt)/[ρ(Flt)+ρ(Pyr)] and ρ(IcdP)/[ρ(IcdP)+ρ(BghiP)]>0.5, ρ(BaA)/[ρ(BaA)+ρ(Chr)]>0.35 suggested common sources in these environments, mainly from vehicle emissions and coal combustion. 3) Inhalation cancer risk (19.8×10 -6, California Environmental Protection Agency(CalEPA)-based method; 15.6×10 -4, World Health Organization (WHO)-based method) was found to be highest in the roadside environment, about 1.4 and 3.6 times those for buses and subways, respectively. 4) PAHs were more enriched under the roadside and bus environments. Exposure to PAHs and the health risks obviously increased in the roadside environment during days with elevated PMconcentrations.